Using Italian vocabulary - Danesi, Marcel, 1946- (Cambridge University Press, 2003)
Using Italian Vocabulary provides the student of Italian with an in-depth, structured approach to the learning of vocabulary. It can be used for intermediate and advanced undergraduate courses, or as a supplementary manual at all levels - including elementary level - to supplement the study of vocabulary.